The Inlfuence of Internal Audit on Fraud Prevention at Perum Bulog (Company Logistic Business Agency) Bandung City - Yuli Sri Rahayu (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
This study aims to determine the effect of internal audit on fraud prevention at Perum Bulog Bandung. The factors tested in this study are the independent variable is internal audit, while the dependent variable is fraud prevention. The research method used is the verification method. The population in this study were employees of the Internal Supervisory Unit (SPI). The sampling technique used is a non-probability sampling technique with a total sampling technique so that the number of samples is 34 employees. The analytical method used is simple linear regression analysis using the SPSS Version 25.00 program. The results of the study indicate that internal audit and fraud prevention are included in the fairly good category. In addition, the results of hypothesis testing show that internal audit has an effect on preventing fraud at Perum Bulog, Bandung City. The magnitude of the influence of internal audit in contributing to fraud prevention is 31.5%.